Psychological Characteristics of Students with a Penchant for Gender Perfectionism (Journal of Educational Sciences, 2026)
Over the past few decades, the concept of "perfectionism" has become the subject of numerous studies in the field of psychology and education. Perfectionism is understood as a personality trait, especially among students. The phenomenon is characterized by the desire for ideal and perfection, for example, in educational activities, on the way to a successful career. High expectations from society and parents reinforce the development of this character trait. Having perfectionism can motivate and inspire people to achieve better outcomes and success, but at the same time can negatively affect mental well-being in young people. The constant pursuit of the ideal can lead to chronic stress, depression and anxietyDespite interest in this topic, the relationship of perfectionism with what personal characteristics and characteristics affect its development is not well understood. The purpose of this study is to study the psychological characteristics of students with a tendency to perfectionism in the gender aspect. The study involved 100 students of higher educational institutions of the city of Almaty - 50 male students and 50 female students. The following psychodiagnostic methods were used: Hewitt & Flett Multidimensional Perfectionism Scale (MPS), SDTP (Short Differential Test of Perfectionism) by A. Zolotareva, Freiburg Personality Inventory (FPI-R). The study found significant differences in the manifestations of perfectionism in male and female students: male students had higher levels of socially prescribed perfectionism than female students. In women, high levels of perfectionism correlate more strongly with negative personality characteristics. It has been shown that the average level of perfectionism is adaptive and favorable for the psychological state of students. The results obtained can serve as a basis for the development of practical measures of psychological support for students, as well as for further understanding of theoretical and applied issues related to the manifestation of perfectionism.Keywords: perfectionism, gender aspect, psychological features, students, anxiety, self-esteem.